2024
DOI: 10.3390/foods13030478
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Rheological Properties of Dough Obtained by Partial Substitution of Wheat Flour with Freeze-Dried Olive Pomace

Patricia Dahdah,
Roberto Cabizza,
Maria Grazia Farbo
et al.

Abstract: Mediterranean countries are known for their high-quality olives and the production and consumption of olive oil. Olive pomace (OP), the major by-product of olive oil extraction, is receiving attention for its potential as a functional compound in food products, reflecting its physiology- and health-promoting attributes. This study assessed the physico-chemical characteristics of OP obtained from two Sardinian olive cultivars, Bosana and Semidana, and the effect of OP incorporation on the baking performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The increase in dough stability and decrease in softening degree can be attributed to the hydroxyl groups present in phenolic compounds, which can directly bond with wheat flour proteins and affect the functional properties of the food. The study by Dahdah et al [72], on the other hand, showed a decrease in dough development time and dough stability with increasing olive pomace content. However, at low supplementation levels (1-3%, depending on the olive variety), the changes in dough stability were insignificant compared to the control sample.…”
Section: Dough Rheologymentioning
confidence: 90%
See 3 more Smart Citations
“…The increase in dough stability and decrease in softening degree can be attributed to the hydroxyl groups present in phenolic compounds, which can directly bond with wheat flour proteins and affect the functional properties of the food. The study by Dahdah et al [72], on the other hand, showed a decrease in dough development time and dough stability with increasing olive pomace content. However, at low supplementation levels (1-3%, depending on the olive variety), the changes in dough stability were insignificant compared to the control sample.…”
Section: Dough Rheologymentioning
confidence: 90%
“…This decrease was mainly attributed to gluten dilution, requiring lower amounts of water to achieve the optimal consistency, and the higher content of oil, which can coat both starch and gluten, leading to a reduction in water absorption. In the study conducted by Dahdah et al [72], a reduction in water absorption was noted as the supplementation levels of olive pomace increased, particularly with additions exceeding 2%. They utilized freeze-dried powder (<500 µm) obtained from olive pomace (from two olive cultivars) to supplement wheat flour.…”
Section: Dough Rheologymentioning
confidence: 93%
See 2 more Smart Citations